Penerapan Tepid Water Sponge Pada Anak dengan Kejang Demam - Abdillah, Uqbah; Merina, Nuning Dwi (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Introduction: Febrile seizures are a common condition in children that can cause concern for parents and healthcare professionals. Fever seizures are the brain's response to rapidly rising body temperature. In some cases, febrile seizures can cause a child's body temperature to rise dramatically, increasing the risk of complications. Nursing interventions in febrile seizures are crucial to manage symptoms and prevent complications that may arise. One intervention that can be applied is the use of tepid water sponge. This study aims to implement nursing care in children with a history of febrile seizures. Methods: This study used a case study design with a nursing approach. Study subjects were children with febrile seizures. Data collection uses a pediatric Nursing Care format which includes Assessment, Diagnosis, Intervention, Implementation, and Nursing Evaluation. Results: Based on the assessment, the patient appeared limp, the skin was palpated warm with a body temperature of 37.9'C, nursing diagnoses of Hyperthermia, Risk of Injury, Nausea. Planning and implementation are giving tepid water sponge, evaluation shows a decrease in temperature in children. Conclusion: The problem is resolved characterized by a decrease in fever in children and preventing the risks that will occur in pediatric clients with a history of febrile seizures. It is hoped that health workers can improve nursing skills in providing nursing care to pediatric clients with a history of febrile seizures.